Haemophagocytic lymphohistiocytosis in critically ill adults: a single-centre retrospective ICU cohort study - Haar, Markus; Stadermann, Alina; Roedl, Kevin; Tintelnot, Joseph; Krusche, Martin; Gleibs, Fabian; Nierhaus, Axel; Ahmadi, Paymon; Kluge, Stefan; Witte, Hanno; Wichmann, Dominic (Frontiers in Medicine, 2025)
BackgroundHaemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory syndrome characterised by uncontrolled immune activation and multi-organ dysfunction. Whilst initially described in paediatric populations, HLH is increasingly recognised in critically ill adults, often triggered by malignancies, infections, or autoimmune diseases.MethodsThis single-centre retrospective study analysed 43 adult patients with HLH admitted to the ICU between 2008 and 2024. Clinical characteristics, laboratory parameters, organ support requirements, and outcomes were assessed. Temporal trends in routine parameters surrounding HLH diagnosis were also evaluated.ResultsThe median age was 45 years (IQR: 33–60), and 65% were male. Respiratory failure (62.8%) and sepsis (41.9%) were the leading causes of ICU admission. Disease severity was high, with a median SOFA score of 14 (IQR: 11–17), and ICU mortality reached 65.1%. Invasive mechanical ventilation was required in 83.7% of patients, and continuous renal replacement therapy in 72.1%. Ferritin levels were markedly elevated, with a median peak of 25,045 μg/l (IQR: 12,771–94,586), with 93% of patients exceeding 6,000 μg/l. The median HScore was 245 (IQR: 210–273) and did not differ significantly between survivors and non-survivors (p = 0.64).ConclusionHLH in adult ICUs carries high mortality and demands extensive organ support. Existing diagnostic scores provide limited bedside guidance, highlighting the need for ICU-specific validation and improved prognostic markers.